Pengaruh Motivasi Kerja dan Beban Kerjaterhadap Komitmen Karyawan dengan Kepuasan Kerja sebagai Variabel Moderasi (Studi pada PT. PLN Persero UP3 Kudus) - Kristian Jajang Saputra; Yuli Budiati; Paulus Wardoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of work motivation and workload on employee commitment, with job satisfaction as a moderating variable at PT PLN (Persero) UP3 Kudus. The research method used was a descriptive quantitative approach with a census technique involving 124 respondents. Data collection was carried out using a 7-point Likert scale questionnaire. Data analysis was carried out using multiple linear regression and a moderation test using SPSS version 26. The results showed that work motivation and workload had a positive and significant effect on employee commitment, and that job satisfaction also had a positive and significant effect on employee commitment. However, job satisfaction did not moderate the relationship between work motivation and workload on employee commitment. The conclusion of this study is that increased work motivation, proportional workload, and job satisfaction can increase employee commitment, but job satisfaction does not act as a moderating variable in this relationship. Keywords: Work Motivation, Workload, Job Satisfaction, Employee Commitment, Moderation